2022
DOI: 10.2174/1568009622666220705095403
|View full text |Cite
|
Sign up to set email alerts
|

Dextran Sulfate Inhibits Angiogenesis and Invasion of Gastric Cancer by Interfering with M2-type Macrophages Polarization

Abstract: Purpose: To explore the effect of dextran sulfate (DS) on the angiogenesis, invasion, and migration of gastric cancer cells through interfering with the polarization of M2-type macrophages. Methods: The infiltration of M2-type macrophages and microvascular density in gastric cancer and paracancerous tissues were analyzed using immunohistochemistry and immunofluorescence. The effects of DS on M2-type macrophages and the angiogenesis in metastatic tumors were investigated in the nude mice intraperitoneal metas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Guo et al. validated the promoting effects on the angiogenesis of M2 TAMs in GC 60 . Moreover, the promoting effects of M2 TAMs on angiogenesis in GC were confirmed by Tang et al 83 .…”
Section: The Role and Mechanism Of Tams In Gcmentioning
confidence: 85%
See 4 more Smart Citations
“…Guo et al. validated the promoting effects on the angiogenesis of M2 TAMs in GC 60 . Moreover, the promoting effects of M2 TAMs on angiogenesis in GC were confirmed by Tang et al 83 .…”
Section: The Role and Mechanism Of Tams In Gcmentioning
confidence: 85%
“…52 Guo et al validated the promoting effects on the angiogenesis of M2 TAMs in GC. 60 Moreover, the promoting effects of M2 TAMs on angiogenesis in GC were confirmed by Tang et al 83 Notably, high microvessel density (CD105) was observed in the tissues with high infiltration of M2 TAMs using immunohistochemical (IHC) staining. 124…”
Section: Tams Enhance Angiogenesis In Gcmentioning
confidence: 85%
See 3 more Smart Citations